2011
DOI: 10.1128/iai.05692-11
|View full text |Cite
|
Sign up to set email alerts
|

Role for the Src Family Kinase Fyn in Sphingolipid Acquisition by Chlamydiae

Abstract: The bacterial obligate intracellular pathogen Chlamydia trachomatis replicates within a membrane-bound vacuole termed the inclusion. From within this protective environment, chlamydiae usurp numerous functions of the host cell to promote chlamydial survival and replication. Here we utilized a small interfering RNA (siRNA)-based screening protocol designed to identify host proteins involved in the trafficking of sphingomyelin to the chlamydial inclusion. Twenty-six host proteins whose deficiency significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Because sphingolipid acquisition is a critical step in the development of obligate intracellular chlamydial organisms (18,19), there are multiple compensatory mechanisms, as evident in the role of Src family kinase Fyn (62) and CERT (63,64), an endoplasmic reticulum-associated ceramide transfer protein, in chlamydial sphingomyelin acquisition. Data in this study identify the first SNARE protein involved in sphingomyelin trafficking to the chlamydial inclusion; however, there are other proteins involved in vesicle fusion that have been demonstrated to play a role in chlamydial sphingomyelin acquisition, such as small GTPase Rab proteins, which are involved in vesicle formation and trafficking (65).…”
Section: Discussionmentioning
confidence: 99%
“…Because sphingolipid acquisition is a critical step in the development of obligate intracellular chlamydial organisms (18,19), there are multiple compensatory mechanisms, as evident in the role of Src family kinase Fyn (62) and CERT (63,64), an endoplasmic reticulum-associated ceramide transfer protein, in chlamydial sphingomyelin acquisition. Data in this study identify the first SNARE protein involved in sphingomyelin trafficking to the chlamydial inclusion; however, there are other proteins involved in vesicle fusion that have been demonstrated to play a role in chlamydial sphingomyelin acquisition, such as small GTPase Rab proteins, which are involved in vesicle formation and trafficking (65).…”
Section: Discussionmentioning
confidence: 99%
“…A recent siRNA screen to identify host proteins required for SM acquisition by C. trachomatis has also implicated Src family kinases (SFK), specifically Fyn, in SM acquisition (Mital and Hackstadt, 2011a). Activated Fyn and Src kinases localize in discrete microdomains at the inclusion that are enriched in cholesterol and overlap with a subset of Incs, including IncB, Inc101, Inc222 and Inc850 (Mital et al ., 2010).…”
Section: Signalling and Lipid Transportmentioning
confidence: 99%
“…Activated Fyn and Src kinases localize in discrete microdomains at the inclusion that are enriched in cholesterol and overlap with a subset of Incs, including IncB, Inc101, Inc222 and Inc850 (Mital et al ., 2010). Depletion of Fyn decreases C6‐NBD‐sphingolipid retention by both the inclusion and EBs; however, depletion of Fyn alone does not impair production of infectious progeny, indicating that SM trafficking mediated by Fyn signalling functions redundantly with other lipid trafficking pathways (Mital and Hackstadt, 2011a). SFK regulate microtubule‐ and dynein‐dependent trafficking of the inclusion to the microtubule organizing centre (MTOC) (Mital and Hackstadt, 2011b), therefore, it is speculated that Fyn may mediate linkage of the inclusion to the microtubule network and thereby intersect SM containing vesicles trafficking along microtubules.…”
Section: Signalling and Lipid Transportmentioning
confidence: 99%
“…Previous studies have demonstrated that in chlamydial infected cells labeled with C 6 -NBD-ceramide, the chlamydial inclusion intercepts Golgi-derived NBD-sphingomyelin (Hackstadt et al, 1996; Hackstadt et al, 1995; Moore et al, 2008; Wolf and Hackstadt, 2001). Most recently, methods developed from these initial studies helped to identify a role in SRC family kinases in the trafficking of sphingomyelin to the chlamydial inclusion (Mital and Hackstadt, 2011). Basic Protocol 1 outlines the steps for labeling cells with C 6 -NBD-ceramide to study lipid transfer and metabolism.…”
Section: Basic Protocol 1 Labeling Cells With C6-nbd-ceramide To Examentioning
confidence: 99%